Detection of malaria in goats and sheep - Yudhi Ratna Nugraheni; April Hari Wardhana; Aan Awaludin; Joko Prastowo; Surya Widyarsi; Yosua Lede Pono (Politeknik Negeri Jember, 2023)
Plasmodium species, as the causative agent of malaria, are a significant concern in livestock production. This study aims to investigate the presence of malaria parasites in small ruminants comprised of goats and sheep. Plasmodium infections in ungulates do not cause malaria in humans. However, they might have anopheline mosquitoes as the same vector of this parasite. This study uses molecular techniques, nested PCR, to detect Plasmodium infections in small ruminants, as traditional microscopic examination may lead to misdiagnosis. The results show that Plasmodium infections were found in goat samples from Sumba Barat Daya, Nusa Tenggara Timur, with a prevalence of 7.41% based on nested PCR assay. Notably, Plasmodium was not detected through microscopic examination, underscoring the sensitivity of molecular techniques. It should be noted that none of the goats tested positive for malaria based on microscopic examination, suggesting extremely low parasitemia levels. This study emphasizes the importance of understanding Plasmodium infections in small ruminants, shedding light on their impact on animal health and their potential role in local transmission patterns. The sample size in this study is limited. Further research with larger samples and expanded geographical scope is recommended to comprehensively understand Plasmodium prevalence in small ruminants.